An Effective Chemical Deterrent for Invasive Cuban Treefrogs - Steve A. Johnson; Monica E. McGarrity; Christina L. Staudhammer (Human-Wildlife Interactions, 2017)
Introduced vertebrates have a variety of impacts on ecosystems and economies, and many cause problems for humans. One such problem is the loss of electrical power when invasive animals cause short circuits in power-transmission equipment. Cuban treefrogs (Osteopilus septentrionalis) are known to cause power outages and are a nuisance to humans when they invade homes and defecate on doors and windows. These large, slightly toxic treefrogs were introduced into Florida from the Caribbean. They now occur throughout the peninsula of Florida and are spreading to other states in the Southeast. We used refuge choice experiments to test the effectiveness of Sniff ’n’ StopTM animal deterrent to exclude Cuban treefrogs from enclosed spaces, such as utility switchgear boxes. We found that the deterrent was effective and showed potential as a low-cost means to prevent frog-related power outages and reduce conflicts with residents in the urbanized areas preferred by these invasive frogs